Toxic Leadership and Empowering Leadership: Relations with Work Motivation - Semedo, Carla (2022)
Purpose: The present study aims to verify the association between two opposing models of leadership, toxic and empowering, and the different dimensions of work motivation. Participants and Methods: Three questionnaires (Toxic Leadership Scale, Empowering Leadership Questionnaire, and Multidimensional Work Motivation Scale) were applied to 408 workers. Cluster analysis was performed. Results: Cluster analysis produced eight clusters based on the different con gurations of leadership dimensions, namely coercive, centralizer, false paternalistic, toxic role model, coach, narcissistic-empowering, toxic, and empowering. Those clusters relate differently to work motivation dimensions. Conclusion: The pro les with higher scores in empowering leadership dimensions are more generally related to autonomous regulation (identi ed and intrinsic work motivation). The pro les with higher toxic leadership dimensions are more related to amotivation and controlled regulation (extrinsic work motivation). One pro le stood out: the narcissistic-empowering pro le that combines high scores in narcissistic leadership and empowering leadership dimensions. This pro le unexpectedly relates signi cantly to autonomous regulation. This study contributed to the knowledge of the work motivation dimensions concerning empowerment and toxic leadership. Therefore, it contributes to deepening the nomological network of the concepts and providing inputs to human resource processes suitable to improving the organizational results and the workers’ quality of life.